Respuesta :

Simplifying 49x^2 + -9 = 0
Reorder the terms: -9 + 49x^2 = 0
Solving -9 + 49x^2 = 0 Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '9' to each side of the equation. -9 + 9 + 49x^2 = 0 + 9
Combine like terms: -9 + 9 = 0 0 + 49x^2 = 0 + 9 49x^2 = 0 + 9
Combine like terms: 0 + 9 = 9 49x^2 = 9
Divide each side by '49'. x^2 = 0.1836734694
Simplifying x^2 = 0.1836734694
Take the square root of each side: x = {-0.428571429, 0.428571429}

hope this helps!!